Perception of The Ability To Understand Calculus Concepts in Online Learning - Malay, Irvan; Bara, Galih Alam; Anam, Hery Hairul; Faisal, Faisal; Prasetio, Anugrah (CV Raskha Media Group, 2025)
This descriptive research analyzes the perception of Panca Budi University students' perception of the implementation of online Calculus learning. Calculus is admittedly difficult, exacerbated by pretest results that show that 60% of students do not understand learning. The results of the study show a comprehensive negative perception of Calculus online learning. This negative perception was studied from three aspects: Content of Material (87% negative), Learning Interaction (75% negative), and Learning Environment (40% negative). Although the presentation of teaching materials by lecturers is considered positive, it is not able to change the negative perception of the material itself. Students argue that the most effective learning process is through face-to-face and direct explanations. This negative perception is a serious challenge, also rooted in the low ability to recall previous learning. Efforts can be focused on reintegrating more effective face-to-face methods, or if online is to be maintained, it is necessary to adapt the learning model that is able to create a more interactive, supportive, and adequate environment to facilitate in-depth problem-solving exercises.